Effects of asphalt emulsion on calcium silicate hydrate gel: Morphology and porosity. Issue 1 (15th October 2020) - Zeng, Xiaohui; Zhu, Huasheng; Lan, Xuli; Liu, Haichuan; Long, Guangcheng; Ma, Cong
Abstract: In this paper, calcium silicate hydrate (CSH) gel and calcium silicate hydrate doped with asphalt emulsion (EACSH) were synthesised using Na2 SiO3 9H2 O, Ca (NO3 )2 4H2 O, NaOH, deionised water and anionic asphalt emulsion. N2 isothermal adsorption, X‐ray diffraction (XRD) and scanning electron microscopy (SEM) were used to study the effect of asphalt emulsion on morphology and porosity of CSH. The Frenkel–Halsey–Hill (FHH) model was used to analyse the surface fractal characteristics. The results showed that the asphalt emulsion had little effects on the change of specific surface areas and the distribution of the micropores for CSH gel, which may be related to the absence of the intercalation reaction and the "opening" effect. The asphalt emulsion could promote the formation of mesoporous hydrated calcium silicate and decreased the number of mesopores in CSH gel but had little effects on the macroporous and microporous structure of CSH. The calculation results of the FHH model showed that the fractal characteristics between CSH and EACSH were different. The emulsifier may adsorb CSH gels result in globular accumulation state.